Peran Fasilitator Pendamping Access To Knowledge (A2K) Program Sahabat Daya Terhadap Perkembangan Usaha Nasabah Bank BTPN Syariah - Lely Rahmasari; Baiq Desthania Prathama (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
Certified independent study and internship program (MSIB) is one of the independent campus programs designed to ensure get the best competencies, the latest competencies, and leading competencies to face the world in the future. Companion facilitators and the Sahabat Daya program are certified apprentices organized by PT. Bank BTPN Syariah Tbk, and is fully supported by the ministry of education and culture ristekdikti under the auspices of the Kampus Merdeka initiative. This companion facilitators program is carried out directly, which means meeting face to face with productive underprivileged women/mothers (customer) to learn together in order to increase the capacity or skills of customers in the field of entrepreneurship. Sahabat Daya is the realization of Bank BTPN Syariah commitment to increase customer capacity in asustainable manner by providing opportunities for growth and more meaningfull life. Bank BTPN Syariah believes that customer from all these segments do not only need access to finance and financing. But also increase their capacity in various fields so they can have a better life